The Teaching of Speech and Language Process as a Form and Communicative Speaker’s Typology - Cherwinski, Piotr (Respectus Philologicus, 2003)
The article is devoted to a problem of methodical application of speakers’ typological characteristics in a teaching process of language and speech. The question of necessity and possibility of managing the process of teaching through the accommodation of its verbal-speech form to the contact and explicative types of the students is raised. On the basis of valid data three basic parameters of definition of the explicative types, while dividing into their constituent characteristics, are given. The criteria of type’s projection through the manifestation in speech are shown. The possibility of organizing teaching speech and language with regard of the presented types in different audiences (monolingual, bilingual, foreign) is questioned.